Labor institutions and their impact on shadow economies in Europe - Fialová, Kamila (Prague, 2010)
"This paper analyzes the role of labor market institutions in explaining developments of shadow economies in European countries. We use several alternative measures of the shadow sector, and we examine effects of labor institutions on shadow sector in two specific regions: new and old European Union member countries, as their respective shadow sectors exhibited a different development in the last decade. While the share of shadow economy in GDP averaged 27.7% in the new member countries in 1999-2007, the respective share in the old member states stood at 18.0% only. In our paper, we estimate effects of labor market institutions on two sets of shadow economy indicators?shadow production and shadow employment. Comparing alternative measures of the shadow sector allows more granulated analysis of the labor market institutions effects. Our results indicate that the one institution that unambiguously increases shadow economy production and employment is the strictness of employment protection legislation. Other labor market institutions?active and passive labor market policies, labor taxation, trade union density and the minimum wage setting?have less straightforward and statistically robust effects and their impact often diverge in new and old EU member countries. The differences are not robust enough, however, to allow us to reject the hypothesis of similar effect of labor market institutions in new and old EU member states."